Empowering leadership navigating the employee's entrepreneurial orientation through work uncertainty: Evidence from tourism and hospitality industry - Farhan Qadir; Muhammad Farhan Basheer; Shafaq Arif Chaudhry; Rab Nawaz Lodhi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This research investigates the impacts of empowering leadership (EL) on work uncertainty (WU) and employee's entrepreneurial orientation (EO) and its dimensions (risk-taking, pro-activeness, and innovativeness). Furthermore, this study also exploring the intervening role of work uncertainty in the connection between empowering leadership and entrepreneurial orientation and its dimension. The data (n=271) were gathered from individuals employing in hospitality and tourism industry of Pakistan by utilizing a time- lag research approach. Using AMOS software for data analysis, findings suggested that empowering leadership is meaningfully related with work uncertainty and individual's entrepreneurial orientation. Similarly, work uncertainty mediates the relationship between empowering leadership and entrepreneurial orientation and its dimensions. This study suggests that empowering leadership can be an effective tool for encouraging employee's entrepreneurial orientation. Therefore, managers and leaders of hospitality and tourism sector, who aim to achieve employee's entrepreneurial orientation need to induce empowering leadership in their organization. The article bridges the gap relating to factors and antecedents that impact individual's entrepreneurial orientation in a time lag research design. This research is one of the pioneer studies which examining, how empowered leadership affects entrepreneurial orientation, with employing work uncertainty as a mediating role. The practitioners of tourism and hospitality industry such as investors, managers, employees and other stakeholders, will find this study quite useful as well.
Keywords: 330; Empowering leadership; work uncertainty; entrepreneurial orientation; self- determination theory; tourism and hospitality industry